What methods are used to apply positive deviance within healthcare organisations? A systematic review. Issue 3 (20th November 2015) - Baxter, Ruth; Taylor, Natalie; Kellar, Ian; Lawton, Rebecca
Abstract : Background: The positive deviance approach focuses on those who demonstrate exceptional performance, despite facing the same constraints as others. 'Positive deviants' are identified and hypotheses about how they succeed are generated. These hypotheses are tested and then disseminated within the wider community. The positive deviance approach is being increasingly applied within healthcare organisations, although limited guidance exists and different methods, of varying quality, are used. This paper systematically reviews healthcare applications of the positive deviance approach to explore how positive deviance is defined, the quality of existing applications and the methods used within them, including the extent to which staff and patients are involved. Methods: Peer-reviewed articles, published prior to September 2014, reporting empirical research on the use of the positive deviance approach within healthcare, were identified from seven electronic databases. A previously defined four-stage process for positive deviance in healthcare was used as the basis for data extraction. Quality assessments were conducted using a validated tool, and a narrative synthesis approach was followed. Results: 37 of 818 articles met the inclusion criteria. The positive deviance approach was most frequently applied within North America, in secondary care, and to address healthcare-associated infections. Research predominantly identified positive deviants and generated hypotheses about how they succeeded. The approach and processes followed were poorly defined. Research quality was low, articles lacked detail and comparison groups were rarely included. Applications of positive deviance typically lacked staff and/or patient involvement, and the methods used often required extensive resources. Conclusion: Further research is required to develop high quality yet practical methods which involve staff and patients in all stages of the positive deviance approach. The efficacy and efficiency of positive deviance must be assessed and compared with other quality improvement approaches. PROSPERO registration number: CRD42014009365.